Trends in the incidence of work-related traumatic limb amputations in South Korea from 2004 to 2013. (August 2019) - Jeon, Inpyo; Leigh, Ja-Ho; Ro, Jun-Soo; Ro, Young Sun; Lee, Seung Hak; Shin, Hyung-Ik; Bang, Moon Suk
Background: Epidemiological data for work-related traumatic limb amputations are limited worldwide, particularly incidence trends related to workplace characteristics. Objectives: To investigate nationwide incidence rates and trends for amputations according to industry and establishment size. Study design: Retrospective cohort study. Methods: Incidence rates were calculated using workers' compensation claims in South Korea from 2004 to 2013. Age–sex standardization was conducted, and trends related to workplace characteristics were statistically analyzed using the chi-square test. Results: The overall incidence rate was 38.8 claims per 100, 000 workers. Decreasing trends over time in age–sex standardized incidence were observed. Most claims occurred in manufacturing and construction industries. Incidence within the manufacturing decreased significantly ( p < 0.001), but not in the construction ( p = 0.130) industry. Small-sized establishments (<50 employees) accounted for 77.8% of claims. Incidence in small establishments significantly decreased between 2004 and 2013 ( p < 0.001). Conclusion: A decreasing incidence rate for traumatic amputations in manufacturing and small establishments may imply that preventive measures have been successful in South Korea. If so, these strategies may be useful for other fast-growing Asian economies. Further research is needed to identify the causes of traumatic amputations according to industry and establishment size. Clinical relevance: Trends in the incidence rate of work-related traumatic limb amputations related to workplace characteristics can provide useful information for policy makers to improve prevention strategies.